2014
DOI: 10.1021/jp410275y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Structure Determination Methods for Intrinsically Disordered Amyloid-β Peptides

Abstract: Intrinsically disordered proteins (IDPs) represent a new frontier in structural biology since the primary characteristic of IDPs is that structures need to be characterized as diverse ensembles of conformational substates. We compare two general but very different ways of combining NMR spectroscopy with theoretical methods to derive structural ensembles for the disease IDPs amyloid-β 1–40 and amyloid-β 1–42, which are associated with Alzheimer’s Disease. We analyze the performance of de novo molecular dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
115
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(123 citation statements)
references
References 84 publications
6
115
2
Order By: Relevance
“…Consistent with earlier reports, 17,94,95 we find that the ensembles in all force fields are in poor agreement with RDCs (see Figure S19). It has been suggested that the conformational ensembles of IDPs may be affected by the presence of alignment media used in measurements of RDCs.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Consistent with earlier reports, 17,94,95 we find that the ensembles in all force fields are in poor agreement with RDCs (see Figure S19). It has been suggested that the conformational ensembles of IDPs may be affected by the presence of alignment media used in measurements of RDCs.…”
Section: Resultssupporting
confidence: 86%
“…Ensembles consistent with experimental data have also been selected from conformations obtained using MD simulations. [16][17][18] Ball et al compared knowledge-based ensemble selection approaches to ensembles obtained using de novo MD simulations. 17 Because IDP ensembles are severely underdetermined (that is, there are many degrees of freedom and relatively few experimental observables), cross-validation and care in avoiding overfitting are essential to these approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…63 Ball et al compare 2 different ways of combining NMR spectroscopy with theoretical methods and apply them to determining the structural ensembles for amyloid b. 64 Finally, Sara et al demonstrate the use of novel NMR and EPR techniques to characterize weak protein-protein complexes, such as those seen in IDP interactions. 65 Single-molecule force spectroscopy as a method to study IDPs was also covered this quarter.…”
Section: Experimental Approaches For the Analysis Of Intrinsic Disordermentioning
confidence: 99%
“…IDPs are defined by their lack of a single stable tertiary structure [11,12], and often have a function for which their disorder is essential [13]. It has been suggested that biomineralisation proteins are the most disordered functional protein class [14], perhaps owing to required adaptability for multi-stage matrix assembly [13], interaction with ions [15] and selectivity of chemical environment in which assembly occurs [16].…”
Section: Introductionmentioning
confidence: 99%